Current Concepts in the Use of Voluma, Volift, and Volbella. (November 2015) - Goodman, Gregory J.; Swift, Arthur; Remington, B. Kent
Abstract : Background: Hyaluronic acids (HAs) are very popular temporary fillers with a very good safety record. Improvements and adaptations in clinical use are continuing. Methods: We have assessed the available literature to investigate the relatively new Vycross technology that uses a mixture of high- and low-molecular-weight HAs with a relatively low but varying HA concentration with enhanced cross-linking to produce a number of products that have differing clinical indications. Results: Voluma has the highest HA concentration at 20 mg/mL, a high G prime translating into lift capacity and cohesivity keeping the product capable to lift vertically adding structure, form, and volume, whereas Volbella has much lower concentration at 15 mg/mL, a lower G prime and cohesivity allowing it to be used in more a horizontal spreading fashion enabling a superficial approach to lips, lines, and more subtle depressions. Volift at 17.5 mg/mL HA is half way between the 2 other products, allowing more subtle lift capacity but retaining an element of spread making it a useful agent for the perioral region in general and in the treatment of fine lines. Conclusion: A range of products has been released that allows different components of facial structure, volume, and lines to be adequately addressed.